Improving Speaking Skill of the Seventh-Grade Students through ESA - Yogiswara, I Putu Ananda; Ari Wiryadi Joni, Dewa Ayu; Mantra, Ida Bagus Nyoman (Journal on Studies in English Language Teaching (JOSELT), 2025)
Speaking skills are crucial for effective communication and a cornerstone of language learning. However, many seventh-grade students at SMPN 2 Ubud in the academic year 2024/2025 exhibited deficiencies in their speaking skills, characterized by shyness and fear of making mistakes. This research aimed to investigate whether the implementation of the ESA (Engage, Study, Activate) technique could significantly improve the speaking skills of these students. A classroom action research approach was employed, involving two cycles of data collection through pre-tests, post-tests, and student questionnaires. The results demonstrated a significant improvement in the students' mean scores from the pre-test to the post-test, indicating the effectiveness of the ESA technique. 1 Furthermore, the questionnaire revealed positive student feedback regarding the implementation of this approach. Based on these findings, it can be concluded that the ESA technique is an effective strategy for enhancing the speaking skills of seventh-grade students at SMPN 2 Ubud in the academic year 2024/2025.